Design of an Impact Evaluation of Sunaula Hazar Din. - Bhattarai, Manav. (Tufts University. Tisch Library., 2016)
This presentation evalutates the impact of a World Bank project, taking numerous perspectives as it does so. Delievered on Day 2 of the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Keywords: DIME, World Bank.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy